2011
DOI: 10.1627/jpi.54.1
|View full text |Cite
|
Sign up to set email alerts
|

コロイド状および担持ナノ粒子の設計─その合成,構造解析と触媒作用─

Abstract: Fabrication of nanoparticle (NP)-based materials have attracted much attention in the field of catalysis, because their special properties lie between those of single metal species and bulks. In this review article, we highlight our recent progress in the development of promising NPs-based catalysts designed by precise architecture that enable efficient and selective chemical reactions and can be easily separated and recyclable. Firstly, novel strategies to fabricate well-controlled catalytically active metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…For instance, Wang et al reported smart supramolecular nano-enzymes with temperature-driven switching properties have been successfully constructed by the self-assembly of supra-amphiphiles formed by the cyclodextrin-based host-guest chemistry [9]. Although reviews have also examined the application of this approach in various industrial fields [17][18][19][20][21], no reports have examined its applicability to automotive paints. However, since cyclodextrin, which tends to be used for these inclusion compounds, has high hydrophilicity, it is presumed that the compounds described in these reports would not satisfy the high-performance requirements of automotive paint films.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wang et al reported smart supramolecular nano-enzymes with temperature-driven switching properties have been successfully constructed by the self-assembly of supra-amphiphiles formed by the cyclodextrin-based host-guest chemistry [9]. Although reviews have also examined the application of this approach in various industrial fields [17][18][19][20][21], no reports have examined its applicability to automotive paints. However, since cyclodextrin, which tends to be used for these inclusion compounds, has high hydrophilicity, it is presumed that the compounds described in these reports would not satisfy the high-performance requirements of automotive paint films.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these drawbacks, small NPs have generally been used on suitable supports, such as polymers, metal oxides, mesostructured materials, and carbon materials, which also provide unique catalytic functions including site isolation of active metal NPs, cooperative action by several sites, and synergic effects owing to the strong metal‐support interactions 9a. 11…”
Section: Introductionmentioning
confidence: 99%
“…This will prevent the necessity of additional purification techniques to remove the catalyst from the waste stream making it a “greener” catalyst comparing to previous approaches. This area has deserved a lot of attention and there have been several good reviews on the subject of catalysts immobilised onto magnetic nanoparticles [ 6 , 16 , 25 , 26 , 27 , 28 , 30 ]. The current review considers only the most recent developments in this field during the last few years.…”
Section: Introductionmentioning
confidence: 99%